Settlement of Marital Problems By Using The Traditional Institutions of Married Brothers - Latupono, Barzah; Kuahaty, Sarah Selfina; Pesulima, Theresia Louize (SASI, 2023)
Introduction: Many marital problems arise in the household so that many households end their marriages in court, but settlement in court faces many obstacles due to the accumulation of unresolved marriage cases.Purposes of the Research: To find out and analyze the settlement of marital disputes using the customary institutions of married brothers in Central Maluku district.Methods of the Research: This research was conducted using an empirical juridical approach which is a descriptive study of qualitative analysis. This research attempts to describe the settlement of marital problems by using the traditional marriage system in Haruku Island District, Central Maluku Regency.Results of the Research: The results of the study show that the settlement of marriages using the customary institution of married brothers in the Haruku Island sub-district is very beneficial for husbands and wives who have problems in their marriage which can be resolved by their married relatives, both world problems and their afterlife problems that exist in their married life so that no longer are settlement issues settled in court.